Reputasi Penjamin Emisi, Return Awal, Return 15 Hari Sesudah IPO, dan Kinerja Perusahaan Satu Tahun Sesudah IPO di BEJ - NASIRWAN NASIRWAN (The Indonesian Journal of Accounting Research, 2013)
The objectives of this study are threefold. First, this study empirically examines whether the underwriter reputation, auditor reputation, percentage in offering, company age, company size, offering value, and  standard deviation of returns are associated with initial returns, 15 day returns after IPO, and company performance one year after IPO. Second, this study evaluates whether the ranking of underwriters’ and auditors’ reputation by measure of Johnson-Miller (JM) is different from those by the measure of Carter-Manaster (CM) in the context of initial returns, 15 day returns after IPO, and company performance one year after IPO. Finally, this study evaluates the consistency between the findings of this study and those of previous studies.The empirical results show that underwriters’ reputation ranked by JM is positively associated with initial returns at the day of offering. This is partly consistent with hypothesis 1. However, when returns were measured for 15 days after the IPO, both JM and CM measures result in statistically significant positive association between reputation and returns. The percentage of stock offering and the value of offering also provide statistically significant negative association with returns. For returns measured one year after IPO, underwriters’ reputation ranked by CM is positively associated with one year performance. When all variables are included in the model, only reputation ranked under CM is statistically significant. The value of stock offering is also statistically significant with a negative sign. for company performance one year after IPO. From various proxies in ranking the reputation of emission guarantor in the three hypotheses above, CM measure shows the best result to control the reputation of underwriter, especially in the context of 15 day return after IPO and performance one year after IPO.